Inuvik, Canada's new Arctic town - Pritchard, Gordon B. (Polar Record, 1962)
During the summer of 1952, investigations were carried out in the town of Aklavik to assess its possibilities for expansion through the addition of educational, health, and administrative facilities, and the construction of an airstrip to serve the community. The unsatisfactory local conditions uncovered by those investigations led the Advisory Committee on Northern Development to recommend that Aklavik should be moved to a new and more stable site. This recommendation was accepted in December 1953 and the Advisory Committee was given the responsibility of selecting a new site.